EXPERIENCE OF UKRZALIZNYTSIA MODERNIZATION OF COMMERCIAL ELECTRIC POWER ACCOUNTING. STIMULATION OF THE CONSUMERS THE WHOLESALE ELECTRICITY MARKET FOR THE MODERNIZATION OF ACCOUNTING AND CONTROL THEIR OWN SCHEDULE CONSUMPTION - Karpenko, S. Ya. (Science and Transport Progress, 2006)
Experience of commercial account of Ukrzalyznytsy electric power and modernization of account and adjusting of the own graph of consumption is described in the article.